Developing Infrastructure in Nigeria: Why is the Cost so High? - Olayeni, Patience Tunji; Lawal, Philip Olayemi; Amusan, Lekan Murtala (Mediterranean Journal of Social Sciences, 2012)
The total cost of infrastructure in normal circumstances is expected to be the sum of the cost of materials, labor, siteoverheads, equipment/plant, head office cost and profit but in many parts of the world particularly in Nigeria, there are othercosts to be allowed for. This study seeks to investigate and report the other costs to be allowed for, which are the reasons whythe cost of infrastructure is so high. A sample of 70 respondents comprising of construction clients, consultants and contractorswere randomly selected and data were gathered using a set of questionnaire to identify the reasons for high cost ofinfrastructure. Spear man rank order correlation was used to analyze the study hypothesis. The findings revealed cost ofmaterials, incorrect planning, wrong method of estimation, contract management and fluctuation of material prices as the fivemost important factors affecting cost of infrastructure. It was also found that construction clients, consultants and contractors donot generally agree on the severity rank of the factors affecting cost of infrastructure in Nigeria. While it is recommended that thegovernment should develop adequate frameworks for monitoring and controlling cost of infrastructure, consultants especiallycost experts should ensure that they make use of accurate estimating methods and that contractors should employ adequateplanning and scheduling techniques because proper planning and scheduling is the key to utilizing project resources andminimizing wastes.